O EXERCÍCIO ÉTICO NA CLÍNICA: O DRAMA ENTRE O DEVER E O DEVIR - MARQUES, Raul Marcos Carvalho Cantanhede (2020)
We develop, in a Deleuzian dramatic reading, the conception of a possible clinical position that is composed in a dialogical relationship between a Deleuzian philosophy centered on ethics and a psychology freed from moralism. This philosophy stands out as a system of affirmation of ways of life as necessary; such psychology is dedicated to clinical work whose relationship with the client is updated through ethical exercise. Deconstructing rationalist, theoretical and abstract hypostasies, conditions of possibility are generated so that the client can perceive and affirm the protagonism of ethical and moral existential modulations within their plane of immanence. Soon we are facing a clinical position whose proposal moves towards understanding and not judgment; neither does it want the power to accuse what being is, nor the duty to defend negatives in order to define what it is not. Only to announce a process: the being goes constant movement and transformation.